EVALUATION OF THE EFFECTIVENESS OF LOCAL CLAY FROM EBONYI STATE, NIGERIA AS A SUBSTITUTE FOR BENTONITE IN DRILLING FLUIDS. Issue 1 (March 2019) - S.G, S.G; Ogiriki, Ogiriki; S.O, S.O; Afolabi, Afolabi; F, F; Bodunde, Bodunde; E.J, E.J
No abstract available